The Influence of FOMO on Impulse Buying In Bali - Suryani Livia Prawira; Ni Wayan Yuli Anggreni (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the influence of Fear of Missing Out (FOMO) on impulse buying behavior among the people of Bali. The research uses a quantitative approach with purposive sampling, where respondents were selected based on the criteria of residing in Bali, being at least 17 years old, and having engaged in impulsive purchasing. Data were collected through an online questionnaire using a Likert scale and analyzed with SPSS 27 through validity tests, reliability tests, classical assumption tests, and simple linear regression analysis. The results show that FOMO has a positive and significant effect on impulse buying, indicating that the higher the level of FOMO experienced by individuals, the greater their tendency to make unplanned spontaneous purchases. These findings align with the Theory of Planned Behavior (TPB), which explains that subjective norms and social pressure can influence intentions and consumer behavior. This study is expected to contribute to businesses, consumers, and future researchers in understanding psychological factors that affect impulsive buying behavior in the digital era.